Restoring Amazonia: promoting Eco-Efficient land use alternatives = Restauración de la Amazonia: fomento de alternativas Eco-Eficientes para uso del suelo - Jarvis, Andy; Lavelle, Patrick M. (International Center for Tropical Agriculture, 2010)
The Amazon Basin, home to approximately half of the world’s tropical forests and a quarter of global biodiversity, has experienced alarming rates of deforestation, land degradation, and loss of ecosystem services since the 1960s. These processes have largely been driven by unsustainable, low-productivity agriculture, which has left a legacy of persistent rural poverty and over 30 million hectares of abandoned or severely degraded land. The vast deforested and degraded regions of the Amazon are in great need of restoration by ‘eco-efficient’ land use alternatives that efficiently utilize resources to produce sustainable livelihood benefits while also providing environmental services. Promising examples of eco-efficient agriculture that have the potential to restore Amazonian landscapes include production systems such as improved fallows, multistory agroforestry systems, silvo-pastoral systems, and improved pastures. Although uptake of these strategies in the Amazon remains low, opportunities to promote these more sustainable land uses are quickly emerging, as concern for environmental issues increases, new markets for environmental services open up, consumer interest in niche and novel products rises, and market access improves. CIAT is working to improve the environmental and socioeconomic conditions in the Amazon by developing eco-efficient options for restoring degraded landscapes and by supporting the long-term success of these land use alternatives.